Progress on AlGaN-based solar-blind ultraviolet photodetectors and focal plane arrays - Cai, Qing (Light Sci Appl, 2021)
Solar-blind ultraviolet (UV) photodetectors (PDs) have attracted tremendous attention in the environmental, industrial, military, and biological fields. As a representative III-nitride material, AlGaN alloys have broad development prospects in the field of solar-blind detection due to their superior properties, such as tunable wide bandgaps for intrinsic UV detection. In recent decades, a variety of AlGaN-based PDs have been developed to achieve high-precision solar-blind UV detection. As integrated optoelectronic technology advances, AlGaN-based focal plane arrays (FPAs) are manufactured and exhibit outstanding solar-blind imaging capability. Considering the rapid development of AlGaN detection techniques, this paper comprehensively reviews the progress on AlGaN-based solar-blind UV PDs and FPAs. First, the basic physical properties of AlGaN are presented. The epitaxy and p-type doping problems of AlGaN alloys are then discussed. Diverse PDs, including photoconductors and Schottky, metal–semiconductor–metal (MSM), p-i-n, and avalanche photodiodes (APDs), are demonstrated, and the physical mechanisms are analyzed to improve device performance. Additionally, this paper summarizes imaging technologies used with AlGaN FPAs in recent years. Benefiting from the development of AlGaN materials and optoelectronic devices, solar-blind UV detection technology is greeted with significant revolutions.